A rare cause of the abdominal pain in a 48‐year‐old woman with a history of prior colon surgery. Issue 4 (8th February 2020) - Makker, Jasbir; Abbas, Hafsa; Kumar, Kishore; Bhandari, Peter; Patel, Harish
Abstract: Fecal retention in the blind loop of end to side colonic anastomosis can lead to fecaloma without significant colonic distension. Imaging study and colonoscopy examination can assist in making a definite diagnosis. Revision surgery is the last choice when colonoscopic extraction fails. Abstract : Fecal retention in the blind loop of end to side colonic anastomosis can lead to fecaloma without significant colonic distension. Imaging study and colonoscopy examination can assist in making a definite diagnosis. Revision surgery is the last choice when colonoscopic extraction fails.